Nilai Ekonomi Islam: Pengaruh IPM, UMP, Pengangguran Terdidik terhadap Kemiskinan Multidimensi Sumbagsel Tahun 2015–2024 - Khadizah, Helpa Khadizah; Bahrudin , Moh; Setyanto , Alief Rakhman (Li Falah: Journal of Islamic Economics and Business, 2026)
Multidimensional poverty remains a critical development issue because it encompasses deprivation in income, education, health, and living standards. This study aims to analyze the effects of the Human Development Index (HDI), Provincial Minimum Wage (PMW), and unemployment on multidimensional poverty in Southern Sumatra, Indonesia. A quantitative explanatory approach with panel data was employed. The study covered five provinces in Southern Sumatra during 2015–2024 using a census sampling technique. Secondary data were obtained from Statistics Indonesia (BPS) and related government institutions. Data were analyzed using panel data regression with the Fixed Effect Model. The results show that HDI has a significant negative effect on multidimensional poverty, indicating that improvements in human development contribute to reducing deprivation. PMW also significantly affects multidimensional poverty, highlighting the role of wage policies in improving welfare. However, unemployment does not have a significant effect. Simultaneously, all variables significantly influence multidimensional poverty. These findings support the Capability Approach and suggest that strengthening human development and wage policies can enhance multidimensional poverty reduction strategies.